Pengaruh Self-Control terhadap Internet Gaming Disorder pada Mahasiswa di Kota Bandung - Agam Gumilang; Muhammad Ilmi Hatta (UNISBA Press, 2023)
Abstract. The number of online game players continues to increase each year. This serves as evidence of the progress and accessibility of technology, which is becoming easier for anyone to access. Individuals can experience internet gaming disorder due to high engagement in online gaming activities. Self-control is known to play a role in influencing internet gaming disorder. However, previous research has yielded inconsistent results. This study aims to determine the extent of the influence of self-control on internet gaming disorder. The sample used in this research consisted of 102 individuals, aged between 18-25 years, who were college students and players of First Person Shooter online games. The sampling technique employed in this study was purposive sampling. The measurement tools used in this study were the Internet Gaming Disorder Scale and the Self-Control Scale. Based on the results of statistical tests, the significance value of the regression coefficient between self-control and internet gaming disorder was found to be sig = 0.189 > 0.05. Therefore, it can be concluded that self-control does not have a significant effect on internet gaming disorder. Additionally, based on the R-square score of 0.017, it can be stated that self-control only accounts for 1.7% of the variance in internet gaming disorder. Abstrak. Pemain game online jumlahnya semakin meningkat setiap tahunnya. Hal tersebut merupakan bukti dari kemajuan dan kecanggihan teknologi yang semakin mudah diakses oleh siapapun. Individu dapat mengalami internet gaming disorder dikarenakan aktivitas online gaming yang tinggi. Kontrol diri diketahui berperan memberikan pengaruh terhadap internet gaming disorder. Namun, terdapat inkonsistensi hasil dari penelitian-penelitian yang telah dilakukan sebelumnya. Penelitian ini bertujuan untuk mengetahui seberapa besar pengaruh self-control terhadap internet gaming disorder. Sampel yang digunakan pada penelitian ini berjumlah 102 orang berusia antara 18-25 tahun yang merupakan mahasiswa pemain game online jenis Frist Person Shooter. Teknik sampling pada penelitian ini menggunakan teknik purposive sampling. Pada penelitian ini, alat ukur yang digunakan adalah Internet Gaming Disorder Scale dan Self-Control Scale. Berdasarkan hasil uji statistik, nilai signifikansi koefisien regresi antara self-control terhadap internet gaming disorder sebesar sig = 0.189 > 0.05. Maka dapat diambil kesimpulan bahwa self-control tidak berpengaruh signifikan terhadap internet gaming disorder. Selain itu, berdasarkan skor r square = 0,017 dapat dikatakan bahwa self-control hanya berpengaruh sebesar 1,7% terhadap internet gaming disorder.